Claudin‐16 Deficiency Impairs Tight Junction Function in Ameloblasts, Leading to Abnormal Enamel Formation. (20th October 2015) - Bardet, Claire; Courson, Frédéric; Wu, Yong; Khaddam, Mayssam; Salmon, Benjamin; Ribes, Sandy; Thumfart, Julia; Yamaguti, Paulo M; Rochefort, Gael Y; Figueres, Marie‐Lucile; Breiderhoff, Tilman; Garcia‐Castaño, Alejandro; et al.
ABSTRACT: Claudin‐16 protein (CLDN16) is a component of tight junctions (TJ) with a restrictive distribution so far demonstrated mainly in the kidney. Here, we demonstrate the expression of CLDN16 also in the tooth germ and show that claudin‐16 gene ( CLDN16 ) mutations result in amelogenesis imperfecta (AI) in the 5 studied patients with familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC). To investigate the role of CLDN16 in tooth formation, we studied a murine model of FHHNC and showed that CLDN16 deficiency led to altered secretory ameloblast TJ structure, lowering of extracellular pH in the forming enamel matrix, and abnormal enamel matrix protein processing, resulting in an enamel phenotype closely resembling human AI. This study unravels an association of FHHNC owing to CLDN16 mutations with AI, which is directly related to the loss of function of CLDN16 during amelogenesis. Overall, this study indicates for the first time the importance of a TJ protein in tooth formation and underlines the need to establish a specific dental follow‐up for these patients. © 2015 American Society for Bone and Mineral Research.